2022
DOI: 10.1371/journal.pntd.0010986
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2D6 (CYP2D6) and glucose-6-phosphate dehydrogenase (G6PD) genetic variations in Thai vivax malaria patients: Implications for 8-aminoquinoline radical cure

Abstract: Background Primaquine and tafenoquine are the only licensed drugs that effectively kill the hypnozoite stage and are used to prevent Plasmodium vivax malaria relapse. However, both primaquine and tafenoquine can cause acute hemolysis in glucose-6-phosphate dehydrogenase (G6PD)-deficient people with varying degrees of severity depending on G6PD variants. Additionally, primaquine efficacy against malaria parasites was decreased in individuals with impaired cytochrome P450 2D6 (CYP2D6) activity due to genetic pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…A study with 88 patients infected with vivax malaria from the province of Yala. in Thailand, identi ed that about 51.1% of these patients were intermediate metabolizers of CYP2D6 and had reduced enzymatic activity, thus putting them at risk of therapeutic failure and reinforcing the need to implement G6PD and CYP2D6 testing as an aid in the use of 8-aminoquinolines for the elimination of vivax malaria (14,35). In gUM, the clinical outcome with PQ remains undetermined (14); however, it is suggested that the CYP2D6 ultra-rapid phenotype is less susceptible to recurrence and PQ failure (18).…”
Section: Discussionmentioning
confidence: 99%
“…A study with 88 patients infected with vivax malaria from the province of Yala. in Thailand, identi ed that about 51.1% of these patients were intermediate metabolizers of CYP2D6 and had reduced enzymatic activity, thus putting them at risk of therapeutic failure and reinforcing the need to implement G6PD and CYP2D6 testing as an aid in the use of 8-aminoquinolines for the elimination of vivax malaria (14,35). In gUM, the clinical outcome with PQ remains undetermined (14); however, it is suggested that the CYP2D6 ultra-rapid phenotype is less susceptible to recurrence and PQ failure (18).…”
Section: Discussionmentioning
confidence: 99%
“…In gIMs, the active metabolites may not achieve the desired response, and the clinical picture would depend on the severity of the CYP2D6 enzymatic alteration, body weight and the total dose administered. A study with 88 patients infected with vivax malaria from Thailand identified that about 51.1% of these patients were intermediate metabolizers of CYP2D6 and had reduced enzymatic activity, thus putting them at risk of therapeutic failure and reinforcing the need to implement G6PD and CYP2D6 testing as an aid in the use of 8-aminoquinolines for the elimination of vivax malaria [ 15 , 35 ]. In gUM, the clinical outcome with PQ remains undetermined [ 17 ]; however, it is suggested that the CYP2D6 ultra-rapid phenotype is less susceptible to recurrence and PQ failure [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study had some limitations, such as the low number of patients included, due to the scarcity of well-described severe hemolytic cases followed up with exams and updated phone contact record; clinical and laboratory data were collected retrospectively. The future implementation of pharmacogenetic testing for better patient management is needed, The implementation of pharmacogenetic tests would help in better patient management, as the metabolism of PQ by different enzymatic phenotypes of CYPs can contribute to severe hemolysis, thus increasing the risks of hospitalizations [ 5 , 21 , 34 , 35 ], in addition to the importance of diagnosing G6PDd before treatment with any of the 8-aminoquinolines [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%